Rural Transformation in India in the Decade of Miraculous Economic Growth. (July 2016) - Ohlan, Ramphul
The study empirically measures the pattern and extent of rural transformation in India using a comprehensive assessment system based on three multidimensional indices, namely rural development index, rural transformation index and urban–rural coordination index. The constructed rural transformation index shows that rural India has undergone a sweeping transformation during the decade of sharp economic growth. The transformation that occurred in India is accompanied by an improvement in the rural development level. The analysis indicates that India's urban–rural coordination has slightly declined between 2001 and 2011. In addition, large regional disparities in rural transformation are shown. Based on findings, it is argued that policies aimed at region-specific rural transformation types may be an effective way to shape a more integrated urban–rural development pattern in India.